Hubungan Konsep Diri dengan Ide Bunuh Diri pada Mahasiswa di Kota Padang - Putra, Trio Kurnia; Nurmina, Nurmina (Indo Publishing, 2026)
College students experience a transition from adolescence to early adulthood, marked by academic, social, and psychological demands, potentially leading to mental stress, including suicidal ideation. Suicidal ideation is the thought/desire to end one's life, which may be accompanied by planning. Self-concept refers to an individual's perception, assessment, and understanding of themselves, formed through experience and interaction. This study aims to determine the relationship between self-concept and suicidal ideation among college students in Padang City. The study used a quantitative correlational. The study subjects were 398 undergraduate students aged 18–24 in Padang City, using a purposive sampling technique. Data collection on suicidal ideation was based on the Beck Scale for Suicide Ideation (Beck et al., 1979) adapted from the Beck Scale for Suicide Ideation (Beck et al., 1979) and the self-concept scale based on Sari's (2020) aspects developed by Prasetyo (2025). The results of the correlation analysis showed a significant negative relationship between self-concept and suicidal ideation (r = -0.666; p < 0.001). Therefore, the higher the self-concept, the lower the tendency for suicidal ideation. This finding confirms the importance of strengthening self-concept as a protective factor in efforts to prevent suicidal ideation in students.